Effect of date palm and polypropylene fibers on the characteristics of self-compacting concrete: comparative study - Dounia Derdour; Mourad Behim; Mohammed Benzerara (Fracture and Structural Integrity)
This article presents the results of a comparative experimental study on the influence of date palm fibers to replace polypropylene fibers used as reinforcement in self-compacting concrete (SCC). Indeed, the use of polypropylene fibers makes it possible to reduce the plastic shrinkage of concrete. Date palm fibers have mechanical characteristics (tensile strength and elasticity modulus) largely sufficient to replace polypropylene fibers. The use of natural fibers has several advantages, they are natural, renewable, have no effect on the environment and require little energy for their transformation unlike synthetic fibers. In this comparative study, polypropylene fiber is used as a control material and date palm fiber as a study material. The results obtained show that the two types of fibers decrease the fluidity and the compressive strength, increase the flexural strength and decrease the shrinkage. Date palm fibers delay the appearance of cracks more than polypropylene fibers. Date palm fibers guarantee the best results of SCC in fresh and hardened state.